STRATEGI BERSAING OPTIMALISASI POTENSI BISNIS PORANG - Budiman, Arief (Journal Business Administration: Entrepreneurship and Creative Industry, 2023)
The porang plant (Amorphophallus oncophyllus) is a member of the Araceae family which is generally known as the corpse flower because of its unpleasant flower odor. Porang is a new commodity that can provide added value for both farmers and companies that manage porang. Based on data obtained and reported from Kominfo, it is known that one hectare of porang land can produce 15-20 tons. Porang had been predicted as a leading export commodity, but when the government determined it as a leading commodity, the price of porang actually dropped even more. Many Porang farmers have complained about falling selling prices. Therefore, the main objective of this research is to see how to optimize Porang as a promising business opportunity, making a superior commodity that is feasible to be developed. This study uses a descriptive qualitative analysis tool, with a case study in the Ngrayun Ponorogo area, East Java. The conclusion of this study is that in fact there are several challenges that need to be considered by the government, including (i) increasing production, especially related to the productivity level of porang; (ii) marketing and (iii) Porang's business market structure which tends to be oligopsonic.